STRATEGI DAKWAH MELALUI LEMBAGA PENDIDIKAN ISLAM DI PONDOK PESANTREN AN NAHDLAH MAKASSAAR - Andy Andy (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2020)
One of the da'wah in Indonesia is Islamic educational institutions, namely Islamic boarding schools which consistently carry out their da'wah activities by shaping the knowledge, attitudes, and behavior of students in accordance with the guidance of Islamic teachings. The existence of An Anahdlah Islamic Boarding School in the midst of the people of Makassar City is very strategic for the development of Islamic da'wah, especially in urban communities that have been built by modernization. By maintaining the diversity of traditions as one of the teaching values, Islamic Boarding School An Nahdlah has challenges in carrying out Islamic da'wah.